Kurdish Press Treatment of the Economic Crisis in the Kurdistan Region of Iraq - صادق حمەغریب حمەصاڵح; جواد محمد امین عیسا (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The role of Kurdish Media in solving economic crisis in Kurdistan Region An explanatory study for Rudaw weekly From )2017/12/25-2017/1/2( By Dr. Sadiq Hama Gharib Hama Salih – Salahadin University Asst: Jawad Mohammed Amin Essa – Lebanese French University Summary" The origin of media is back to long time ago and has witnessed massive trends over time in terms of roles and impacts and type of media as well and the environment. The main role of media is its impact during crisis and solving the crisis through (Media crisis management). This is the main subject of this research where how Kurdish media role to solve crisis in the Kurdistan region. For this study we have specified a weekly media for knowing how they work to overcome economic crisis in Kurdistan region. The study consists of three parts, in the first part it is about the methodology including the research problem, objectives and significant. In the second part, has three parts, type, specification and directions of media including role of media in solving crisis, then principles of media during crisis. The research found that the way Kurdish media tries to solve crisis is not based on scientific method, and the sample of the research is for economic sectors and how to solve the economic crisis